What Makes Free Will Free: The Impossibility of Predicting Genuine Creativity - Erinakis, Nikos (Conatus - Journal of Philosophy, 2020)
In this paper I argue that Mill’s ‘Doctrine of Philosophical Necessity’ regarding the human will and action cannot apply on all cases, and that the human mind has potentially the capacity to create freely a will or action that, no matter what kind of knowledge we possess, cannot be predicted. More precisely, I argue against Mill’s attempt of conjunction between the freedom of the will and the ‘Doctrine of Philosophical Necessity’ while I attempt a comparison with the relevant Kantian approach. I then claim that a will cannot be free and be predicted at the same time, as both the elements of freedom and unpredictability of the will are founded on the very process of its formulation as an outcome of genuine creativity. I, thus, attempt to propose a more substantially free view of free will and action than the ones presented by the prominent conceptions.